Challenges and Solutions in the Appointment of Acting Regional Heads (PJ. Kepala Daerah) in Indonesia: A Sharia and Islamic Democracy Perspective - Muhammad Mutawalli Mukhlis; Maskun; Muhammad Saleh Tajuddin; Zuhilmi bin Paidi; Muhammad Mawardi Djalaluddin (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
This study examines the mechanism of appointing regional heads in Indonesia from the perspective of sharia law and Islamic democracy. Using a qualitative approach with descriptive-comparative analysis, the research is based on document analysis and literature review of classical Islamic texts and contemporary Indonesian policies. The results show that although appointing regional heads without direct elections may be necessary under certain conditions to maintain administrative continuity, it raises concerns about legitimacy, transparency, and public participation. From the shariah perspective, the process must uphold justice, trust (amanah), and public welfare (maslahah), in line with Islamic ethical governance. Islamic democracy’s principle of shura (consultation) emphasizes community involvement in leadership selection. The study concludes that a hybrid model integrating meritocracy and shura can offer a solution by promoting democratic accountability and adherence to Islamic values. This contributes to understanding how democratic mechanisms can be harmonized with Islamic political thought in regional governance.